Gaps and opportunities in research on food systems; a micro-institutional analysis of the University of Nairobi - Munialo, Sussy; Onyango, Cecilia Moraa; Lukachi, Jane Ambuko; Wasonga, Oliver Vivian; Maina, Joyce Gichuku; Nzuma, Jonathan Makau; Dawood, Abeda; Sibanda, Lindiwe Majele (Frontiers in Sustainable Food Systems, 2023)
Research conducted on food systems by higher institutions can contribute to sustainable food security and nutrition at a local level and reduce the impact of societal challenges such as malnutrition. Unfortunately, malnutrition itself manifests as hidden hunger causing unintended consequences such as illness negatively affecting economic progress. Traditionally, research in agriculture has not taken a food systems approach which is looking at challenges of food systems from farm to fork (all stages from production to consumption). Therefore, as we embrace the compelling call to transition from agriculture to food systems research approaches, mapping studies at a local level are needed. However, studies on food systems have been carried out at a macro (global or regional level), a micro-perspective investigation is needed to inform future research. A systematic review on existing literature (journals and thesis) was conducted to identify gaps and opportunities in research on food systems undertaken by researchers at the University of Nairobi. Information collected included; 1. institutions (faculties and department at the university, national policy, and international institutions collaborating with university of Nairobi), 2. crop types (cereals, legumes, vegetables, roots and tubers, and nuts), 3. food systems activities (production, postharvest, processing, and preservation, value addition and branding, consuming foods, input and output markets, obtaining nutrients as well as logistics and distribution) driving research on food systems. The contribution of each of the components (institutions, food systems activity and crop type) was also investigated through citation scores. The findings show that low research outputs on food systems were generated by the university of Nairobi compared to selected universities in Africa and across the globe. Research was focused on carbohydrate rich crops (maize, sorghum, cassava, irish potato, sweet potato, and rice) as compared to protective bioactive vitamin crops (vegetables, mango, and beans). This demonstrated low crop diversity and dietary quality. Research priority was given mainly to maize compared to traditional crops such as sorghum, African Leafy Vegetables, cassava and millets. Faculties such as health, science and technology, engineering, and humanities were involved in research in food systems in addition to agriculture, a potential indication of transdisciplinary research. Additionally, there was more collaborative research between university of Nairobi with institutions at a global level than with local institutions. The involvement of policy institutions in research was low, mainly restricted to the discipline of agriculture, production food system activity and in a few crops such as maize, cassava, and medicinal plants. Disparities in research existed along the food systems activities as more attention was focused on production activities. Other food system activities such as harvesting, processing and preservation, consumption, value addition and branding, input and output markets, as well as logistics and distribution activities, received low research priority. Each component (food system activity, crop type and institution) demonstrated contribution to sustainable food security as shown by citation scores. The findings demonstrate skewed focus in food systems research at the university of Nairobi. Agricultural research investment within institutions of higher learning will need to consider all food systems activities, under-researched crops and collaborations that advance transdisciplinary studies to promote inclusive contribution of food systems to food security at a local level. Further studies can focus on developing frameworks to advance transdisciplinary research.